Bending Performance of I-Joists from Jointed Oriented Strand Board (OSB) Web and Laminated Veneer Lumber (LVL) Flanges - Wan Abdul Rahman, Wan Mohd Nazri (2000)
An I-joist is a system that consists of flanges and web components. Both components have to work together as a system in order to match the strength property of solid wood beam. This study was carried out with the objective of obtaining the strength properties of I-joist made from 3 types of jointed oriented strand board (OSB) web ( Finger, L-butt and Nail plate) and 2 types of flanges (solid wood and laminated veneer lumber). Specimens with LVL flanges were found to be almost as strong as specimens with solid flanges. Both materials exhibited non-significant differences in strength properties as an I-joist system because the modulus of rupture (MOR) values of I-joist in this study were not significantly affected by the material of the flange either solid wood or LVL. Among the three types of joints, the I-joist specimen with finger jointed web was the strongest. The weakest joint was madeup ofI-joist specimen with nail plate jointed web. The modulus of elasticity (MOE) of I-joist systems used in this study did not show any significant difference. The analysis of MOE showed that there was no significant difference between the I-joist specimens with solid and L VL flanges of finger jointed web compared to L-butt jointed web, and finger jointed web compared to nail plate jointed web. It was observed that failures in all of the I-joist specimens studied were either in tension or in compression. For specimens of finger and L-butt joints, the failure occurred at the web joints. But for nail plate joints, the failure occurred at the location between two adjacent nail plates connections. OSB web can be produced from the off-cuts of tertiary processing mills that use OSB for other consumer products. Hence, the full use of off-cuts would consequently increase the recovery rate and the net profit. This study could lead to the utilisation of wood residues from an OSB plant as an alternative raw material for the production of web component in I-joists system.